Penentuan perbezaan pendapatan buruh mengikut kemahiran dalam industri pembuatan di Malaysia - Ismail, Rahmah (Universiti Utara Malaysia, 2001)
In Malaysia, the manufacturing sector has been a gradual change in its production process from utilizing a more labor intensive technique to that of more capital intensive. Consequently this change requires a change in skill composition where skilled workers are more demanded by the industries.This has resulted in changes in the wage ratio between skils, which is more favorable to skilled workers. However it is alwavs argued that wage rate do not only depend on the demand or labor. There are other factors that can influence individual income or wages. These include educational attainment,job location, and types of industries and gender. Human capital variables are hypothesized to have a positive relationship with individual labor market earnings. Individual with a high human capital attainment will be more productive; hence, higher reward is paid to them. Also a more urbanized job location and a more capital-intensive industry may offer higher wages to their workers. The more urbanized the place, cost of living becomes higher Industries also will be more competitive in getting workers as a result of high demand. Therefore, employers have to pay higher wages to the workers to cope with this phenomenon. Furthermore, a more capital-intensive industry is expected to be more productive; hence, they are capable of offering more attractive pay to their workers. This paper attempts to test these hypotheses based on a sample survey of 2065 workers in several major industries in Malaysia conducted in 1999. The determinants of labour income differentials will be identified using a regression analysis. Further, the analysis will decompose these factors into several categories to identify which factor contributes most to labour income differentials between skills.